Voltammetry determination of zinc in various types of soil - Rashid, Nurzahirah Mohd (Universiti Sains Malaysia, 2015)
Zinc plays an important role in plant growth as the plant micronutrient. The soil samples were collected from different location to compare the concentration of Zn. Then, the soil sample was digested using H2SO4 and H2O2. Anodic stripping voltammetry (ASV) technique was used to determine the concentration of Zn and the parameters used for the determination of Zn are as follows: start potential: -1.15 V, end potential: -0.7999 V, deposition potential: -1.15 V, deposition time: 90 s, equilibrium time: 10 s, voltage step: 0.005951 V, voltage step time: 0.1 s, sweep rate: 0.0595 V/s, pulse amplitude: 0.05005 V, and pulse time: 0.04 s. One mL acetate buffer with pH 4.64 was used as supporting electrolytes. The peak potential of Zn was found at -0.995 V and the concentration of Zn was determined by the standard-addition method. From ten samples of soil, the underground soil showed the lowest concentration of Zn measured at 2.95 ppm while the concentration Zn in soil from the area of waste incinerator is the highest measured at 57.47 ppm. As the conclusion, ASV technique was successfully applied for the determination of Zn in various types of soil and the concentration of Zn in soil was found to be different from one location to another location.